Clinical history of fibromyalgia: Importance of pain assessment in diagnosis and the impact on patients’ quality of life (Research, Society and Development, 2024)
Objective: to understand the clinical history of fibromyalgia, focusing on the importance of assessing pain in the diagnosis and the impact on patients' quality of life. Methods: this is an integrative review of the literature. The search was carried out in the databases: Portal Regional VHL (LILACS), Sientific Electronic Library Online (SciELO) and National Library of Medicine (PUBMED). The Health Sciences Descriptors (DeCS) were used: “Fibromyalgia”; "Chronic pain"; "Quality of life". Eligibility criteria were: full articles available electronically; written in English, Portuguese or Spanish; published between 2015 and 2023. Abstracts of annals, dissertations, duplicates, ongoing projects, pilot studies or those with conflict of interest were excluded.. Results and discussion: 28 publications were included in this review. It was observed that the main etiological hypothesis involves central sensitization, associated with physical, emotional, genetic and environmental factors. The diagnosis is subject to clinical subjectivity because it does not involve objective clinical-laboratory markers. The impact on quality of life ranges from unrefreshing sleep to sexual problems, psychological disorders and association with other chronic diseases. Management must be multidisciplinary, with non-pharmacological measures, such as physical activity and psychological therapy, and pharmacological measures, with a preference for antidepressants. Conclusion: this is a pathology with significant repercussions on quality of life and the multidisciplinary scope must be considered to elucidate the course of the disease, increase diagnostic accuracy, and effectiveness of treatment/therapeutic arsenal as fundamental factors for maintaining quality of life.